Underpricing of initial public offerings in experimental asset markets - Füllbrunn, Sascha,Neugebauer, Tibor,Nicklisch, Andreas ([University of Luxembourg, Faculty of Law, Economics and Finance, Luxembourg School of Finance], 2019)
The underpricing of initial public offerings is a well-documented fact of empirical equity market research. Theories explain this underpricing with market imperfections. We study three empirically relevant IPO mechanisms under almost perfect market conditions in the laboratory: a stylized book building approach, a closed book auction, and an open book auction. We report underpricing in each of these IPO mechanisms. Uncertainty about the aftermarket behavior may partly explain IPO excess returns but underpricing persists even in the repeated setting where uncertainty is negligible and despite the equilibrium adjustment dynamics, that we observe in the data. The data reveal a market-wide impact of investors' reluctance to sell in the aftermarket at a price below the offering price. We conclude that a behavioural bias similar to the disposition effect fosters IPO underpricing in our setting
Keywords: Graue Literatur; initial public offerings; underpricing; common value auctions; experimental finance; disposition effect; learning